Investigating the Purposes of Thought Experiments: Based on the Students’ Performance (Jurnal Pendidikan IPA Indonesia, 2020)
The objective of this study is to examine the students’ purposes in conducting thought experiments while solving physics problems. There were 12 pre- and in-service physics teachers as the participants in this study and divided into three groups with four students in each. Physics problem-solving activities were used as a context for observing students’ processes in doing TEs. The results of the data analysis showed that there were three types of purposes of the students in doing the TEs during physics problem-solving activities: prediction, verification, and explanation. Therefore, it can be concluded that in the context of problem-solving, students design and run thought experiments as a creative ability tool to (1) predict solutions to the problem, (2) verify whether their hypothesis is correct or incorrect, (3) provide a detailed explanation to their hypothesis. Based on this study, we discuss the differences and similarities in the purposes of scientists and students in doing thought experiments. The importance and implications of thought experiments for current and future physics teachers are also discussed in the last part of this study